Apheresis platelet concentrates contain platelet-derived and endothelial cell-derived microparticles - Rank, Andreas; Nieuwland, R.; Liebhardt, S.; Iberer, M.; Grützner, S.; Toth, Bettina; Pihusch, R. (Vox sanguinis, 2011)
Background and Objectives Microparticles (MP) are membrane vesicles with thrombogenic and immunomodulatory properties. We determined MP subgroups from resting platelets, activated platelets and endothelial cells in donors and apheresis platelet concentrates (PC). Material and Methods MP were double stained with annexin V and CD61 (platelet-derived MP; PMP), P-selectin or CD63 (MP from activated platelets) and CD144 plus E-selectin (endothelial cell-derived MP; EMP) and detected by flow cytometry in platelet donors (n = 36) and apheresis PC (n = 11; Trima™). Results PC contained MP, mainly from resting platelets [93% (90-95)], and minor fractions of PMP from activated platelets [P-selectin+ or CD63+; 4·8% (3·2-7·7) and 2·6% (2·0-4·0)]. Compared to donors, levels of annexin V+ MP, PMP, P-selectin+ and CD63+ MP were 1·7-, 2·3-, 8·6- and 3·1-fold higher in PC (all P < 0·05). During storage (1-5 days), levels of annexin V+ MP and PMP did not increase, although small increases in the fraction of P-selectin+ or CD63+ MP occurred (both P < 0·05). PC also contained EMP, which were 2·6- to 3·7-fold enriched in PC compared to donors (P < 0·05). Conclusions Transfusion of apheresis PC also results in transfusion of HLA-carrying PMP and EMP. This might counteract the aim of reducing transfused HLA load by leucodepletion. The increases in PMP exposing P-selectin or CD63 reflect mild platelet activation during storage. We conclude that in leucodepleted platelet apheresis using fluidized particle bed technology, MP are harvested mainly from the donor by apheresis. Improvement in apheresis technology might reduce MP load.